The explosion at Vector: hoping for the best while preparing for the worst - C Raina MacIntyre; Con Doolan; Charitha De SIlva (University of New South Wales, 2019)
This commentary reviews the implications of the gas explosion at the Russian State Research Centre of Virology and Biotechnology building (Vector) on September 16th 2019. Public health and engineering perspectives are provided on the implications of the explosion causing a physical breach of the building, and the potential for dispersion of pathogens in the surrounding area. A global public health and risk analysis perspective is taken in discussing preparedness planning around this event.